The Catholic Church and Soviet Russia, 1917-1939 - Dunn, Dennis J. (Routledge religion, society and government in Eastern Europe and the former Soviet states, 2017)
Background. Christianity: early history of the Orthodox and Catholic traditions ; East Slavs: Ukrainian, Belorussian, and Russian national identities -- Muscovy, Russian Empire, and the Catholic Church. Ivan the Great to Peter II, 1462-1762 ; Catherine the Great to Alexander III, 1762-1894 ; Nicholas II and the Provisional Government, 1894-1917 -- Soviet Russia and the Catholic Church, 1917-21. Communist government and the Catholic Church, 1917-20 ; Communist government and the Catholic Church, 1921 -- Soviet Russia and the Catholic Church, 1921-24. Communist government and the Vatican, 1921-24 ; Communist government and the Catholic Church, 1922-24 -- Catholic Church and Vatican initiatives, mid-1920s-1930 ; Orthodox-Catholic ties and the Albertyn experiment ; The d'Herbigny mission -- Kremlin, Catholic Church, and collectivization, 1928-33 ; The Soviet government, NEP, and collectivization (4th revolution) ; Correspondence related to collectivization from the Vatican archives -- Soviet Russia and the Catholic Church under Stalin, 1933-34 ; International scene, 1933-34 ; Soviet government and the Catholic Church, 1933-34 -- Soviet Russia and the Catholic Church under Stalin, 1935-39 ; International scene, 1935-39 ; Soviet government and the Catholic Church, 1935-39